Study on the Dynamics of Phase Formation and Degradation of 2D Layered Hybrid Perovskites and Low‐dimensional Hybrids Containing Mono‐functionalized Oligothiophene Cations. Issue 9 (18th June 2021) - Van Gompel, Wouter T. M.; Herckens, Roald; Mertens, Martijn; Denis, Paul‐Henry; Ruttens, Bart; D'Haen, Jan; Van Hecke, Kristof; Lutsen, Laurence; Vanderzande, Dirk
Abstract: Low‐dimensional (2D or 1D) hybrid perovskites are receiving increased attention due to their structural flexibility and enhanced stability compared to their 3D counterparts. Understanding the phase formation and degradation behavior of these materials is crucial towards their use in optoelectronic devices, since different crystal phases possess different optical and electronic properties. In this communication, we study the phase formation and degradation of a series of hybrids containing bithiophene, terthiophene and quaterthiophene derivatives. We show that two crystal phases can be formed for each of these systems, depending on the processing conditions. One phase corresponds to a 2D layered perovskite and the other phase has optical properties corresponding to a dimensionality intermediate between a 2D and a 1D hybrid. Abstract : The formation and degradation behavior of organic‐inorganic hybrids containing different oligothiophene derivatives is studied. We show that two crystal phases can be obtained, a 2D layered hybrid perovskite or a lower‐dimensional hybrid, depending on the processing conditions. The formation behavior of the hybrids is linked to the number of thiophene units in the oligothiophene.